(untitled) (Bangladesh Journal of Botany, 2024)
A field experiment was conducted at agriculture farm, ICAR-Central Institute for Research on Goats (CIRG), Makhdoom, Mathura, Uttar Pradesh during kharif season of 2020. The treatments consist of sole maize, sole cowpea; and intercropping of maize + cowpea in 1 : 1, 2 : 1, 1 : 2, 2 : 2, 3 : 1, 1 : 3 and 3 : 3 row ratios. The results revealed that maximum total green fodder yield, maize and cowpea equivalent yield, Land Equivalent Ratio (LER), Monitory Advantage Index (MAI), net returns and Benefit: Cost ratio were recorded with 2 : 1 row ratio of maize + cowpea intercropping combination followed by 3 : 1 row ratio. The highest value of nitrogen and potassium content both in fodder maize and cowpea were recorded with 1 : 3 row ratios of maize + cowpea intercropping combination. Further, the highest phosphorus content in fodder maize was recorded with 3 : 1 row ratio of maize + cowpea intercropping combination whereas in case of cowpea the highest phosphorus content was recorded with 1 : 3 row ratio of maize + cowpea intercropping combination. Thus, it was found that two rows maize + one row of cowpea (2 : 1) intercropping combination perform best in terms of yield, land use efficiency and profitability of fodder maize and cowpea. Bangladesh J. Bot. 53(2): 235-242, 2024 (June)